2019
DOI: 10.1002/jcb.29551
|View full text |Cite
|
Sign up to set email alerts
|

CFHR3 is a potential novel biomarker for hepatocellular carcinoma

Abstract: Complement factor H‐related 3 (CFHR3) is a protein‐coding gene acting in various diseases. However, its prognostic values of CFHR3 in hepatocellular carcinoma (HCC) are not understandable. Therefore, we present a further study on CFHR3 in HCC. CFHR3 expression data were acquired from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC). We compared the differential expression of CFHR3 between the low‐stage (stage I and II) and high‐stage (stage III and IV) patients with HCC in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
(60 reference statements)
1
20
0
Order By: Relevance
“…Tissue-based approaches were con rmed to be able to characterize the tumor in ltrates in clear cell renal cell carcinoma and primary glioblastoma multiforme, according to previous studies [56,57]. A recent research showed that high-risk cohorts in HCC have higher immune, and stromal scores than that in low-risk cohorts, which was consistent with our results [58].…”
Section: Discussionsupporting
confidence: 89%
“…Tissue-based approaches were con rmed to be able to characterize the tumor in ltrates in clear cell renal cell carcinoma and primary glioblastoma multiforme, according to previous studies [56,57]. A recent research showed that high-risk cohorts in HCC have higher immune, and stromal scores than that in low-risk cohorts, which was consistent with our results [58].…”
Section: Discussionsupporting
confidence: 89%
“…Although the risk effect of FTL was small following adjustment in the multivariate Cox model, the potential role of changes to iron metabolism in the progression of HCC should not be ignored. CFHR3 was demonstrated to exert a protective effect in patients with HCC, and physiologically, CFHR3 is exclusively expressed in normal liver (51). CFHR3 is associated with compliment factor H, which can bind to the C3d region of C3b, regulating the function of compliment system (52).…”
Section: Discussionmentioning
confidence: 99%
“…SNP in PRKAG2 was responsible for advancement of colon and rectal cancer [Slattery et al 2010], but this polymorphic gene may be liable for progression of hepatoblastoma. Enriched genes such as STAB2 [Wu et al 2018], IGF1 [Shi and Teng, 2015], HRG (histidine rich glycoprotein) [Zhang et al 2015], CFHR3 [Liu et al 2020] and CD5L [Aran et al 2018] were linked with proliferation of hepatocellular carcinoma cells, but these genes may be involved in proliferation of hepatoblastoma cells. Methylation inactivation of ADHFE1 was identified with growth of colorectal cancer [Hu et al 2019], but loss this gene may be responsible for progression of hepatoblastoma.…”
Section: Discussionmentioning
confidence: 99%